Resisting invisibility : detecting the female body in Spanish crime fiction - Aramburu, Diana, 1981- (Toronto Iberic, 2019)
"Resisting Invisibility investigates the politics of visibility of women's bodies in Spanish crime fiction. By 'politics of female visibility', the author refers to the textual practices that determine the imperceptibility of women's bodies, including both exposure and erasure. What is at stake in the politics of visibility is the constitution of women as political subjects. The politics of visibility takes on a crucial role in crime fiction because it changes the nature of the story, from a plot that hinges on a female body denied full political participation through various strategies of objectification, to a narrative where the body functions as a critical tool of resistance to pinpoint the ineffectiveness of the legal system. The book provides insight into how authors engage readers with the politics of visibility of the female body through their manipulation of generic conventions involving the gaze and how, in turn, the female body gains or resists visibility."--